68 A personalised approach to obesity consultations: patient perspective and impacts. Issue Volume 23:Issue Supplement 1(2018) (June 2018) - Luig, Thea; Anderson, Robin; Sharma, Arya; Campbell-Scherer, Denise
Abstract : Objectives: Previous research revealed people living with obesity want substantive conversations, personalised assessments and plans. Together with patients and interdisciplinary primary care providers we have created a model for personalised obesity consultations that integrates the 5As of obesity management with the collaborative deliberation model for care. To do this, we used in-depth qualitative methods to examine how people perceive the interpersonal work and content of the consultation; and how this experience impacts their ability to make changes in everyday life to improve their health. Method: We recruited 20 people living with obesity through purposeful sampling to ensure a diversity of patient contexts. Video-recorded one-on-one interventions with a primary care clinician, loosely structured, conversational interviews (patient and clinician) following the consultation, and documentation of intervention impact on patients' self-management through diaries and two follow-up interviews over the course of 6–8 weeks. Thematic analysis using inductive and deductive coding managed in NVIVO11. Results: From the patient perspective an impactful personalised obesity consultation is anchored in the patient's story and a comprehensive root cause assessment, and guided by a whole-person health approach and an orientation on patients' strengths and resources. Using collaborative communication, the care planning focuses on strengthening the patient's capacity to engage in health promoting strategies that fit with the context and fundamental goals of their lives. Impacts that patients experienced include (1) increased confidence, hope, and self-compassion; (2) activation and increased activity levels; (3) increased insight into own barriers and improved coping. Conclusions: We examined patient experiences of the obesity consultation and their everyday life experience of effecting change to improving health and used results to develop a model for a personalised obesity consultation approach. Findings suggest that interpersonal processes that shift the patient towards focusing on whole-person health goals and towards a strength-based, compassionate view of self, effectively support patient activation and self-efficacy for improving health outcomes.